Clinical Profile and Outcome of Mechanically Ventilated Neonates in a Tertiary Level Hospital - Shrestha, Prabina; Basnet, Srijana; Shrestha, Laxman (Journal of Nepal Paediatric Society, 2016)
Introduction: Many sick neonates admitted to neonatal intensive care unit (NICU) require mechanical ventilation but it is associated with various complications and the outcome of neonates is unpredictable. This study aims to identify the indications for mechanical ventilation, complications, co-morbid conditions and outcome of those neonates in terms of survival. Materials and Methods: Retrospective observational study of all neonates who underwent mechanical ventilation from 1 January 2014 to 31 December 2014 in NICU, Tribhuvan University Teaching Hospital. Medical records of the patients were retrieved from hospital record section to collect the relevant data. Results: One-third of admitted neonates in NICU required mechanical ventilation (MV). Commonest indication was severe respiratory distress (70%) followed by perinatal asphyxia (12%) and recurrent apnea (8%). Disease pattern were sepsis (37.2%), RDS of prematurity (17.6%), perinatal asphyxia (11.7%), meconium aspiration syndrome (9.8%), apnea of prematurity (7.8%) and congenital pneumonia (4%). Hospital acquired sepsis was a major complication occurring in 47% patients on mechanical ventilation. Survival rate among neonates on MV was 33%. Survival was better with increasing birth weight and gestational age. Survival was 100% in congenital pneumonia, 50% in perinatal asphyxia, 50% in recurrent apnea, 26% in sepsis, 20% in MAS and 0% in RDS of prematurity. Conclusion: Survival rate of neonates on mechanical ventilation in NICU was 33%. Sepsis was a major problem in NICU, which must be addressed to improve outcome. J Nepal Paediatr Soc 2015; 35(3): 218-223.